Meet the Challenge (African Knowledges and the History Publication since the 1970s)
Moderated and judged competition on scientific knowledge between students from Sam Ford Dennis High School vs. Muslim Congress High School.
Keywords: Competition; Education; Scientific Knowledge; Quiz Show